2009
DOI: 10.1016/j.joca.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effects of running on the deformation of knee articular cartilage and its relationship to biomechanical loads at the knee

Abstract: Limited evidence was found linking biomechanical measures of knee joint loading and observed short-term deformation of knee articular cartilage volume following running. Further enhancement of knee muscle modelling and analysis of stress distribution across cartilage are needed if we are to fully understand the contribution of biomechanical factors to knee joint loading and the pathogenesis of knee osteoarthritis (OA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 30 publications
7
51
3
Order By: Relevance
“…In investigations of volumetric cartilage deformation in response to running, two groups (Boocock et al, 2009; Kersting et al, 2005) observed significant post-activity cartilage deformation in lateral tibial cartilage and femoral cartilage. Notably, medial tibial cartilage deformation was not significant in either study (Boocock et al, 2009; Kersting et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In investigations of volumetric cartilage deformation in response to running, two groups (Boocock et al, 2009; Kersting et al, 2005) observed significant post-activity cartilage deformation in lateral tibial cartilage and femoral cartilage. Notably, medial tibial cartilage deformation was not significant in either study (Boocock et al, 2009; Kersting et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This sustained deformation can be measured using magnetic resonance (MR) imaging immediately before and after loading 11, 13 . Previous studies have used this principle to measure changes in knee cartilage volume as a result of different dynamic activities, including running 8, 20, 21, 30 , drop landings 30 , and knee bends 12 . While these studies contribute important information to the literature, compartmental volumetric changes may not be sensitive to variations in cartilage strain at different locations within the joint.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason for no thickness change could be the absence of controlling for diurnal effects. Unlike the ankle joint, the knee cartilage generally loses thickness and/or volume even after shorter distance running (5 km-20 km) for both trained and recreational runners [13,15,19,22,44] and all these knee studies made efforts to minimize the diurnal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have employed MRI to examine pathological, morphological and/or biochemical changes in response to long-distance running, but such studies have mainly focused on the knee joint [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Many of these studies found significant changes including bone marrow edema (BME), joint effusion and cartilage thickness and volume, but such changes seem to return to baseline after a rest period (1 h to 8 weeks) [13,20,23].…”
Section: Introductionmentioning
confidence: 99%